Creating an interactive E-learning for operation amplifier - Lew, Sue Xin (Nanyang Technological University, 2022)
In University, students are being encouraged to be independent learners. Students do not only follow through with curriculum content but also obtain extra materials online for further knowledge enhancement. By doing so, it inculcates a habit in students to become independent learners in their future jobs. In this Final Year Project, I have developed an interactive e-learning platform for a topic in the school of Electrical & Electronics Engineering. The topic is based on the fundamentals of Operational Amplifiers. In this platform, I have developed interactive practice questions, assignments, a forum and a mini-lab activity regarding a comparator operational amplifier circuit. All these features are developed with the use of Django Framework, as it is a software that combines the elements to develop a website such as HTML, CSS, JavaScript and Python